2011
DOI: 10.1111/j.1464-5491.2011.03403.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing incident diabetes as defined by fasting plasma glucose or by HbA1c. The AusDiab, Inter99 and DESIR studies

Abstract: Diabet. Med. 28, 1311–1318 (2011) Abstract Aim  We examined the ability of fasting plasma glucose and HbA1c to predict 5‐year incident diabetes for an Australian cohort and a Danish cohort and 6‐year incident diabetes for a French cohort, as defined by the corresponding criteria. Methods  We studied 6025 men and women from AusDiab (Australian), 4703 from Inter99 (Danish) and 3784 from DESIR (French), not treated for diabetes and with fasting plasma glucose < 7.0 mmol/l and HbA1c < 48 mmol/mol (6.5%) at inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…Mean HbA 1c differed among studies, more than that of glucose, as we have shown in other analyses [28, 29]. Indeed, in the Japanese-Americans study [24], HbA 1c had a much higher mean than in other studies.…”
Section: Discussionsupporting
confidence: 44%
“…Mean HbA 1c differed among studies, more than that of glucose, as we have shown in other analyses [28, 29]. Indeed, in the Japanese-Americans study [24], HbA 1c had a much higher mean than in other studies.…”
Section: Discussionsupporting
confidence: 44%
“…In strictly non-diabetic subjects, those with HbA1c < 6.5% and by HbA1c ≥ 6.5% and/or treatment, with an area under the receiver operating characteristic curve of 0.84, 0.91 and 0.82 for Inter99, AusDiab and D.E.S.I.R. respectively, indicating that HbA1c was able to discriminate incident diabetes as defined by HbA1c [28].…”
Section: 7% 12/01/2012mentioning
confidence: 99%
“…We have previously studied incident diabetes, where diabetes was defined by treatment and/or HbA1c ≥ 6.5% [28]. In strictly non-diabetic subjects, those with HbA1c < 6.5% and by HbA1c ≥ 6.5% and/or treatment, with an area under the receiver operating characteristic curve of 0.84, 0.91 and 0.82 for Inter99, AusDiab and D.E.S.I.R.…”
Section: 7% 12/01/2012mentioning
confidence: 99%
“…The Australians recommended the use of two cut-off values; ≤ 5.5% to ‘rule-out’ and ≥ 7.0% to ‘rule-in’ diabetes [17]. Variations in prevalence of diabetes [18][22] and prediabetes [23] due to ethnicity have been documented.…”
Section: Introductionmentioning
confidence: 99%